Patient characteristics and management practices in chronic myeloid leukemia in Turkey: reflections from an expert meeting - TOPTAŞ, TAYFUR (My University, 2022)
Introduction The therapeutic landscape of chronic myeloid leukemia (CML) has evolved significantly since the introduction of imatinib. The European LeukemiaNet (ELN) recommendations serve as a guide for diagnosis, treatment, and monitorization of CML, but availability and accessibility of diagnostic tools and medications affect their applicability. Areas covered This article provides an overview of the current clinical management of CML in Turkey with reference to the key outputs of the online expert meeting held in November 2020. The applicability of the ELN 2020 recommendations for treating CML in clinical practice was also discussed. Expert opinion Imatinib is the only reimbursed and the most preferred first-line treatment in CML restricting the upfront use of second-generation tyrosine kinase inhibitors (TKIs), thereby limiting the applicability of treatment-free remission approach in Turkey. The ELN recommendations about using the EUTOS Long-Term Survival (ELTS) score for risk assessment and focusing on patient reported outcomes and quality of life can be enhanced with educational activities. The widespread availability of standardized technical infrastructure for diagnosing and monitoring CML will contribute to better disease management. Establishing a sustainable national database for CML is valuable for observing patient characteristics and disease outcomes as well as the impact of treatment patterns over time.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Hematoloji; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Hematology; HEMATOLOJİ; Klinik Tıp; Klinik Tıp (MED); HEMATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Chronic myeloid leukemia; CML; comorbidities; risk scoring; TKI; tyrosine kinase inhibitor; TFR; treatment-free remission; GENERIC IMATINIB; CML PATIENTS; SURVIVAL; EFFICACY; DISEASE; SAFETY; RECOMMENDATIONS; PROGRESSION; THERAPY; IMPACT